Portafolio management: A critical view beyond Markowitz (2019)
Since its first appearance, the Markowitz model for portfolio selection has been a basic theoretical reference, opening several new development options. However, practically it has not been used among portfolio managers and investment analysts in spite of its success in the theoretical field. This paper presents and discusses the Markowitz’s model limitations modal to its practical implementation, the existence of transaction costs, equilibrium considerations, technical and fundamental analysis importance and the focus on behavioural finance as that of limited rationality, determine that the decision process of the individuals possesses limitations so much cognitive as computing that reduce perfection to their decisions, nevertheless, these theories of behavioural portfolios is possible to consider to be more a descriptive theory of how the investors construct their portfolios, in contrast with the theory of Markowitz's portfolios that is more prescriptive on having tried to instruct the investors how they must their portfolios.